Magnetic, magnetotransport, and optical properties of Al-doped Zn0.95Co0.05O thin films - VENKATESAN, MUNUSWAMY; COEY, JOHN MICHAEL DAVID (American Institute of Physics, 2007)
Thin films of 5% Co-doped ZnO with a range of Al codoping exhibit a band-edge shift, which varies with carrier concentration as n2/3. Carrier effective mass is 0.26me and mobility is ~ 10?cm2?V?1?s?1. The doped films, which contain coherent Co clusters of 4?8?nm in size, exhibit a ferromagnetic moment of 0.3?1.0?B per cobalt. The magnetism is progressively destroyed by Al doping due to a reduction in Co-cluster formation. Magnetoresistance appears below 30?K, but these materials cannot be regarded as dilute magnetic semiconductors.
PUBLISHED
Keywords: Physics